MiRNAs are unlikely to be involved in retinoid receptor gene regulation in pancreatic cancer cells - Yin, Shuai; Bazhin, Alexandr V. (Cellular physiology and biochemistry, 2017)
Background/Aims: Retinoid receptors and retinoic acid were reported to be down-regulated in pancreatic duct adenocarcinoma (PDAC) compared to normal pancreas. Yet the mechanism of the down-regulation of retinoid receptors is not well defined. The aim of this study was to find out whether selected dysregulated miRNAs in PDAC are responsible for the decreased level of retinoid receptors. Methods: Bioinformatics, real-time PCR, western blot analysis as well as molecular manipulation with miRNA in cells of PDAC were carried out. Results: We first performed bioinformatics research to identify conserved target sequences for deregulated miRNAs within the 3’UTR region of retinoid receptor mRNA. This research revealed binding sites for miR-138, -27a, -27b, -206, -613, -9-5p, -27a/b-3p and -27a. Next, we investigated the expression of selected retinoid receptors and miRNAs in PDAC cell lines and in the Human Pancreatic Duct Epithelial (HPDE) cell line. Further, we investigated the effects of modifying expression levels of selected miRNAs using miRNA inhibitors or mimics. We demonstrated that none of these miRNAs can target the selected retinoid receptors in vitro. Conclusions: miR-27a, miR-27b, miR-9, miR10a and miR-10b were up-regulated in PDAC cells compared to HPDE cells. The up-regulation of these miRNAs was not responsible for the down-regulation of RARα, RARβ, RXRα and RXRβ in PDAC cells.